Estrategias de marketing en la Boutique “EIDEM” - Lema Chele, Dayana Lilibeth (2020)
This case study aims to develop marketing strategies in the Boutique "EIDEM". Since the inconveniences presented in the boutique like:  The deficiency of innovation, that is, lack of designs or variety in clothing.  Little publicity on the part of the owner since, he does not know the marketing strategies or techniques necessary to be able to link and sell his merchandise to clients and potential clients. They prevent the growth of the company. It is also notorious that large factors such as competition and in this case the absence of marketing strategies in the "EIDEM" Boutique, making it almost impossible for you to obtain optimal benefits from your sales. The following case study refers to all the elements that are needed to implement the stated objective, which is to determine marketing strategies that are specifically oriented to promotions and advertising to increase the level of sales in the "EIDEM" boutique. " In the same way it is important to mention that the case study has been developed through qualitative research, which served to collect information based on observation about the structure of the company and its environment. Subsequently, quantitative research was applied to facilitate the quantification of the results obtained through a survey, which was carried out on the clients of the "Eidem" Boutique. The research line is production and competitiveness, since all the activities in this case involve a wide interest in the commercialization of clothing. In this case study, the methodology that has been executed and put into practice is the descriptive method, which helped and clearly determined the central or main problems to be solved in the “EIDEM” Boutique. The analytical method was also applied, the same that served to diagnose and previously analyze the daily situations that occur in the boutique, with customers who come to the aforementioned site. In this way, a solid synthesis was obtained, which is necessary during the research process. Emphasizing in turn, the technique of "interview" which is aimed at applying to the owner of the company, being a very useful tool and vital importance for the investigation of this case study. On the other hand, the result obtained from the surveys carried out on the company's customers shows that it does not carry out promotions or discounts when making purchases. In addition to that the designs on the garments do not have much variety or diversity. Due to this, clients feel the need to visit another commercial place where they offer what they need and are looking for. Although it is true the boutique has accounts on social networks, through which it tries to carry out the respective advertising of the merchandise, however, the clients affirm that said networks are not updated frequently.